2020
DOI: 10.21203/rs.3.rs-78047/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosphate Sequestration From Aqueous Solutions Using A Zeolite in The Zinc Form.

Abstract: This work evaluated the ability of a modified zeolite to adsorb phosphates in aqueous solution. The zeolite used for this study was a modified faujasite impregnated with zinc chloride (Z-Zn) on its surface. The experiments were carried out in different stages. Adsorption was performed at different pH of the solution and the zeolitized material was found to be favorable for phosphate adsorption. The adsorption kinetics occurred after 240 minutes and reach the equilbrium, determining chemisorption reactions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Likewise, the O-H bond distance of FAU-Y, closer to the NaH2PO4 molecule, was 1.1 Ǻ, which suggested an interaction between an O atom of the NaH2PO4 molecule and an H atom of FAU-Y. A similar computational study of H3PO4 adsorption on ZSM-5 showed analogous behavior [3,59].…”
Section: Adsorption On Fau-y Modelmentioning
confidence: 72%
See 1 more Smart Citation
“…Likewise, the O-H bond distance of FAU-Y, closer to the NaH2PO4 molecule, was 1.1 Ǻ, which suggested an interaction between an O atom of the NaH2PO4 molecule and an H atom of FAU-Y. A similar computational study of H3PO4 adsorption on ZSM-5 showed analogous behavior [3,59].…”
Section: Adsorption On Fau-y Modelmentioning
confidence: 72%
“…Likewise, the O-H bond distance of FAU-Y, closer to the NaH 2 PO 4 molecule, was 1.1 Å, which suggested an interaction between an O atom of the NaH 2 PO 4 molecule and an H atom of FAU-Y. A similar computational study of H 3 PO 4 adsorption on ZSM-5 showed analogous behavior [3,59]. After full optimization, the O(SHDP)-H(FAU-Y) bond distance was 1.4 Ǻ, and the hydrogen atoms of the molecule were located at a distance of 2.3 Ǻ and 2.1 Ǻ, respectively.…”
Section: Adsorption On Fau-y Modelmentioning
confidence: 72%